2014
DOI: 10.2147/cia.s63596
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of individual dosage of digoxin with calculated concentration

Abstract: BackgroundDigoxin is a frequently prescribed drug, particularly in the elderly population, in which there is an increased prevalence of atrial fibrillation and cardiac failure. With its complex pharmacokinetic profile and narrow therapeutic index, use of digoxin requires regular monitoring of blood levels. Recent evidence suggests that a lower concentration range (0.4–1.0 ng/mL) is preferable in patients with congestive heart failure and a higher range (0.8–2.0 ng/mL) is needed in patients with atrial tachyarr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
2
0
2
Order By: Relevance
“…A study of a Chinese population of patients with HFrEF, AF or both showed a similar correlation between the measured and predicted SDCs using the Konishi equation, which had a correlation coefficient of 0.65 . However, another study of a Caucasian patient population using the Konishi equation showed a lower correlation between the measured and predicted SDCs, which had a correlation coefficient of 0.48 .…”
Section: Discussionmentioning
confidence: 99%
“…A study of a Chinese population of patients with HFrEF, AF or both showed a similar correlation between the measured and predicted SDCs using the Konishi equation, which had a correlation coefficient of 0.65 . However, another study of a Caucasian patient population using the Konishi equation showed a lower correlation between the measured and predicted SDCs, which had a correlation coefficient of 0.48 .…”
Section: Discussionmentioning
confidence: 99%
“…However, despite such efforts, individual factors like age, renal function, and concurrent drug interactions continue to influence digoxin response, mandating personalized dosing strategies and vigilant monitoring [ 34 ]. Studies have revealed substantial variations in serum digoxin concentration levels even among patients sharing similar clinical characteristics, underscoring the imperative for meticulous monitoring and individualized therapy management [ 35 , 36 ]. Recognizing individual variability in digoxin response underscores the necessity for a tailored approach to dosing and monitoring, guided by carefully considering patient-specific factors to optimize therapeutic outcomes and minimize the risk of adverse effects.…”
Section: Reviewmentioning
confidence: 99%
“…На протяжении многих лет дискутируется вопрос о роли сывороточных концентраций дигиталисных пре паратов как в подборе их оптимальных дозировок, так и в диагностике и профилактике дигиталисной интокси кации [2,33,34].…”
Section: контроль сывороточных концентрацийunclassified
“…Сегодня доминирует позиция, что дигиталисная интоксикация остается клиническим диагнозом, а сыво роточные уровни дигиталисных препаратов являются важным подспорьем в верификации ее наличия и тяжести при развитии анорексии, тошноты, рвоты, спутанности сознания, нарушений ритма и проводимости, и других проявлений у больных, получающих дигиталисную тера пию [20,33,34].…”
Section: контроль сывороточных концентрацийunclassified